Traditional activities and general and mental health of adult Indigenous peoples living off-reserve in Canada - Kassem, Hallah; Harris, M. Anne; Edwards-Wheesk, Ruby; Liberda, Eric N. (Frontiers in Public Health, 2024)
We examined associations between traditional Indigenous activities and selfperceived general and mental health in adult Indigenous persons living off-reserve in Canada using the 2012 and 2017 Aboriginal Peoples Surveys (APS), the two most recent datasets. We utilized four traditional Indigenous activities including hunting, making clothes or footwear, making arts or crafts, and gathering wild plants to investigate these self-reported data.Methods: Data from 9430 and 12,598 respondents from the 2012 and 2017 APS, respectively, who responded to 15 questions concerning traditional activities were assessed using multivariable logistic regression to produce odds ratios (OR) and 95% confidence intervals (CI). Covariates included age, sex, education-level, income-level, Indigenous identity, residential school connection, ability to speak an Indigenous language, smoking status, and alcohol consumption frequency.Results: Using the 2012 APS, clothes-making was associated with poor self-reported general (OR=1.50, 95%CI: 1.12-1.99) and mental (OR=1.59, 95%CI: 1.14-2.21) health. Hunting was associated with good mental health (OR=0.71 95%CI: 0.56-0.93). Similarly, 2017 analyses found clothes-making associated with poor general health (OR=1.25, 95%CI: 1.01-1.54), and hunting associated with good general (OR=0.76, 95%CI: 0.64-0.89) and mental (OR=0.69, 95%CI: 0.58-0.81) health. Artmaking was associated with poor general (OR=1.37, 95%CI: 1.17-1.60) and mental (OR=1.85, 95%CI: 1.58-2.17) health.Hunting had protective relationships with mental and general health, which may reflect benefits of participation or engagement of healthier individuals in this activity. Clothesmaking and artmaking were associated with poor general and poor mental health, possibly representing reverse causation as these activities are often undertaken therapeutically. These findings have implications for future research, programs and policies concerning Indigenous health.